Potable Reuse Trends and Challenges: A Conversation With the Editorial Board of the AWWA Water Science Topical Collection on Potable Reuse. Issue 2 (2nd March 2021) - Howe, Kerry J.; Alspach, Brent; Bellona, Christopher; Minton, Julie; Tchobanoglous, George
Key Takeaways: In 2020, AWWA Water Science published a topical collection on potable reuse that aimed to address questions raised by increasing demand for water reuse. Topics in the collection included source water management, pathogen detection and treatment, communications and outreach, and socioeconomics of potable reuse. In an interview, the collection's guest editors discuss the lessons they have learned and the future challenges for potable reuse regulation and research. Improving the feasibility and adoption of potable reuse will require additional research to ensure that it continues to be a safe and reliable water supply.